Operational risk management during disasters: A case of South African tourism small businesses - Wonder Mahembe; Ashley T. Mutezo (Jàmbá)
Small businesses, which were disproportionately affected by the COVID-19 pandemic, often lack the resources for effective operational risk management (ORM), with existing frameworks like International Standardization Organization (ISO) 31000 proving too complex and resource-intensive. There is, however, still minimal research into ORM frameworks tailored to the needs of Small, Micro, and Medium Enterprises (SMMEs) facing disaster risks. This study developed and evaluated a tailored ORM framework for SMMEs to manage operational risk exposures from future disasters like COVID-19. A simplified approach was proposed, consisting of three stages: risk identification or disaster preparedness, risk analysis or disaster learning and risk treatment or building enterprise resilience. The framework was empirically tested on data from 208 tourism industry SMMEs using a quantitative research approach. Correlation analysis, structural equation modelling (SEM) and analysis of variance (ANOVA) tests were used to assess the framework’s applicability to businesses of different ages, sizes and subsectors. Results from correlations and SEM confirmed the proposed ORM framework’s effectiveness in explaining disaster preparedness, learning and resilience for SMMEs. Additionally, ANOVA results showed the framework was equally applicable across business subsectors, but across business age and size, it was not equally applicable. Larger and older businesses were able to implement disaster learning and resilience better than younger and less resourced businesses.